Use and Outcomes of Acute Treatment Strategies in Patients with Severe Aortic Valve Stenosis. Issue 1 (27th December 2021) - Piepenburg, Sven M.; Kaier, Klaus; Olivier, Christoph B.; Bothe, Wolfgang; Heidt, Timo; Jäckel, Markus; Peikert, Alexander; Wolf, Dennis; Zehender, Manfred; Bode, Christoph; Dürschmied, Daniel; von zur Mühlen, Constantin; et al.
Background: This study aimed to evaluate the acute treatment of patients with severe aortic valve stenosis in Germany. Methods and Results: Three treatment strategies in 11, 027 patients acutely admitted due to aortic valve stenosis were compared from 2014 until 2018 using German nationwide records: The annual number of transcatheter aortic valve replacement (TAVR) procedures (1, 294 to 1, 827) and balloon valvuloplasty (BV only) procedures (170 to 233) in patients acutely admitted increased, but surgical aortic valve replacement (SAVR) procedures decreased (426 to 316). In comparison to BV only patients (mean age 81.3; EuroSCORE 23.2) SAVR patients were younger and at lower logistic EuroSCORE (mean age 66.9; EuroSCORE 9.4). Patients treated with TAVR were at comparable age and operative risk (mean age 81.3; EuroSCORE 24.4) as those patients treated with BV only. Primary outcome was in-hospital mortality. Reimbursement was considered secondary outcome. After risk adjustment using multivariable logistic and linear regression analyses, SAVR (OR 0.26 [96%CI 0.16;0.45], p < 0.001) and TAVR (OR 0.38 [0.29;0.49], p < 0.001) were associated with lower risk for mortality compared to BV only. Compared to BV only, hospitalization costs of patients undergoing SAVR were reduced by €5, 578 ([95%CI €8, 023; €3, 133], p < 0.001). TAVR procedures were associated with higher hospitalization costs than BV only (risk-adjusted difference €4, 143 [€2, 330; €5, 926], p < 0.001). Conclusions: BV only was associated with a substantially increased risk of in-hospital mortality in acute patients. We conclude that a definitive aortic valve replacement should be preferred as primary treatment in patients with severe aortic valve stenosis causing an acute admission.